2002
DOI: 10.1046/j.1471-6712.2002.00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Life situation and function in elderly people with and without leg ulcers

Abstract: The majority of elderly patients with leg ulcers live at home and receive treatment for their ulcers within the primary health care system. Little is known about the patients' ability or behaviour in the life situation and how well they manage their daily life at home. The Philadelphia Geriatric Center Multilevel Assessment Instrument (PGC MAI) was used to assess and compare the life situation in 70 patients (mean age 79 +/- 6.5 years) with leg ulcers and in 74 elderly persons (mean age 80 +/- 5.7 years) witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 11 publications
0
26
0
3
Order By: Relevance
“…The state of health might, however, be very important. Wissing, 19 for example, compared the life situation in a Swedish community of 70 elderly patients with leg ulcers with 74 older people without ulcers. She found that the patients with leg ulcers scored lower on the PGCMAI in all domains except the Mobility Domain Index.…”
Section: Discussionmentioning
confidence: 99%
“…The state of health might, however, be very important. Wissing, 19 for example, compared the life situation in a Swedish community of 70 elderly patients with leg ulcers with 74 older people without ulcers. She found that the patients with leg ulcers scored lower on the PGCMAI in all domains except the Mobility Domain Index.…”
Section: Discussionmentioning
confidence: 99%
“…This is a concern, but perhaps reflects the current leg ulceration literature, which suggests that compression is associated with a reduction of pain (Franks et al, 1994;RCN, 2006;Fogh et al, 2008). Furthermore, some patients do not experience a reduction in pain with compression, regardless of correct and appropriate application (Phillips et al, 1994;Chase et al, 2000;Wissing and Unosson, 2002;Nemeth et al, 2004;Hareendran et al, 2005;Heinen et al, 2007;Park et al, 2008;Price et al, 2008). This may create confusion in the nurses applying the compression.…”
Section: Nature Of Pain Associated With Leg Ulcerationmentioning
confidence: 99%
“…Dette påvirket nattesøvnen og førte til dårlige dager. Smerter hos pasienter med venøse leggsår har vist seg å vaere et stort problem (5,9,10,11,15,30), men studier viser også at de verste smertene er knyttet til sår med en arteriell komponent i tillegg (10). Flere pasienter i denne studien hadde høy alder, og en arteriell komponent i leggsåret.…”
Section: Diskusjonunclassified